The Effectiveness of Organizational Communication in Improving the Performance of Public and Private School Committees - Novianty Elizabeth; Poppy Dewi Puspitawaty; Pandji Santosa; Abdorrakhman Gintings (Budapest International Research and Critics University, 2022)
This research is about the existence of school committees which are one of the strengths and driving factors for improving the quality of basic education. Because of the importance of the School Committee's role, the organization's administrators must be able to realize effective organizational communication. The purpose of this study is (1) to find out how much characteristics, understanding, and support for the School Committee management on the effectiveness of communication and (2) to assess whether there is a difference between the performance of the State School Committee and the performance of the Private School Committee in South Tangerang City. This research is located in South Tangerang City. This research uses a survey method with a quantitative approach. The data was obtained through a questionnaire distributed to 425 respondents from 148 Private and Public Elementary Schools and Junior High Schools in South Tangerang City. Data collection uses survey methods with a quantitative approach. The results showed that (1) The communication effectiveness of the School Committee management was considered quite good. The implementation of communication, the preparation of school committee programs and clarity of goals to be achieved are considered quite effective and efficient, while the availability of infrastructure and supervision systems is still considered low. (2) There is a noticeable difference between the performance of School Committee administrators in public schools and the performance of School Committee administrators in private schools where in general the performance of private committee administrators is considered